Tingkat Penanganan Penyakit Jantung di RSUD Arifin Achmad dan Implikasinya bagi Masyarakat - Safira, Siska Dwi (Universitas Nurul Jadid, 2024)
Heart disease remains a leading cause of mortality globally and in Indonesia, emphasizing the importance of effective healthcare services. This study analyzes the level of heart disease management at Arifin Achmad Regional Hospital and its implications for public health in Riau Province. Using a literature review method, secondary data from scientific journals, Ministry of Health reports, and related publications were analyzed. The findings reveal that Arifin Achmad Hospital offers comprehensive heart care services, including intensive care, interventional cardiology, and inpatient and outpatient services. Despite these capabilities, challenges such as limited access for rural communities, a shortage of specialists, and insufficient facilities persist. Addressing these issues requires improving service capacity, adding medical professionals, and developing preventive education programs. Collaboration among hospitals, local governments, and organizations is critical to ensure equitable access and high-quality heart health services in the region